Didactic Infrastructure Management and Curriculum Implementation in Public Universities in Northern Uganda - Bileti, Emmanuel Acidri; Ndawula, Stephen; Kebirungi, Harriet; Rwothumio, Joseph (East African Journal of Education Studies, 2024)
This study investigated the levels of curriculum implementation and didactic infrastructure management in public universities in Northern Uganda. It evaluated the influence of didactic infrastructure management on curriculum implementation in public universities in Northern Uganda. It was hypothesised that didactic infrastructure management has no significant relationship with curriculum implementation in public universities in Northern Uganda. The study was guided by a pragmatic worldview and embraced a concurrent mixed-methods research design. The study used a questionnaire to collect quantitative data from 123 respondents. Qualitative data was collected from 26 participants through interviews. Furthermore, eight focus group discussions were conducted. The quantitative data collected was analysed using descriptive statistics, correlation coefficient analysis and multiple linear regression techniques, while thematic analysis techniques were used to analyse qualitative data. The study revealed that, generally, the levels of curriculum implementation were low and didactic infrastructure management was moderate. The study results showed that didactic infrastructure management had a significant influence on curriculum implementation in public universities in Northern Uganda. The null hypothesis that didactic infrastructure management has no significant relationship with curriculum implementation in public universities in Northern Uganda was rejected. The study concluded that didactic infrastructure management is significant for curriculum implementation. Therefore, it was recommended that public universities in Northern Uganda improve the management of their didactic infrastructure, such as libraries, sports facilities, and halls, to further enhance curriculum implementation, especially in areas of preparation for teaching, content delivery, and assessment of learning